The effect of Governance on development quality partnerships in the Ministry of Hajj and Umrah: Prospective Study in 2022 - Aljohani, Raniah Khaled (Journal of Humanities & Social Sciences, 2023)
The developments in the administrative systems imposed that decision-makers check for the regulations that they work for to achieve the goals. This is what the Ministry of Hajj and Umrah has done to develop its policy for serving the pilgrims. It relied on the governance strategy to support the organizational administrative processes in the ministry. And it was activating oversight is an administrative process that limits administrative and financial corruption in the supporting agencies. Also, the governance supports the process of leadership responsibly inside and outside the ministry by contracting qualitative partnerships with it, it is a system to manage the process of quality partnership. That can be rebuilding the Ministry’s capabilities and preparing for crises. However, the study aimed to measure the discovery of the challenges and formulate a future vision of governance to develop quality partnerships in the Ministry of Hajj and Umrah. The study relied on the qualitative approach. The study used the basic explanatory design, and the qualitative data management program "MAXQDA" was adopted for content analysis. Whatever, the research was applied to the Ministry of Hajj and Umrah in Makkah City. The study concluded many results, the most important of which were that: - The Ministry needs a detailed list and models that govern the work of the parties with which it has a qualitative partnership. -The existence of challenges facing governance and limiting the development of qualitative partnerships, the first of which is the lack of clear standards by the Ministry to ensure the continuity of qualitative partnerships and models for the governance of cruise companies’ services. The research came out with a proposed vision to activate the impact of governance on the development of qualitative partnerships, focusing on organizational, human, and financial performance indicators. The study introduced many recommendations, the most important of which that: To evaluate the application of governance standards in the cruise companies on a regular basis by the competent committee of the Ministry of Hajj and Umrah. The study also recommended that the Ministry of Hajj and Umrah unify efforts in one platform that acts as a mediator between the ministry and the cruise companies.